Estimated Molecular Structure of a Carbon Nanotubec Molecular Heater Based on Binding Properties to a Target Protein. Issue 4 (October 2015) - Kawaguchi, Minoru; Yamazaki, Jun
Background: Carbon nanotubes exhibit strong absorbance in the near-infrared (NIR) region and are considered as potent candidates for hyperthermic therapy because they generate significant amounts of heat upon excitation with NIR light. We prepared a single-walled carbon nanotube (SWNT)/IgG complex to use as a "smart molecular heater" for hyperthermic therapy. Purpose: The aim of the present study was to assess the binding efficiency of DNA-functionalized SWNT/IgG complexes to a target protein. Methods: 3 types of complexes with different lengths of spacer arm chain (13.5, 29, and 56 Å) linked to biotinylated IgG were prepared, and we evaluated the effect of the spacer arm length on the specificity, affinity, and capacity of binding to a target protein. Results: Complexes with longer spacer lengths showed increased binding affinity to a target protein. This could be due to a reduction in steric hindrance by increasing the segmental flexibility of the spacer arm. Conclusions: The results of this study suggested that DNA-functionalized SWNT/IgG complexes could act as a heating nano-device for hyperthermic cancer therapy, and the complexes can bind various types of tumor by modifiying the specific antibody.